Time to move on: Modeling transcription dynamics during an embryonic transition away from maternal control. - Liu, J.; Xiao, Y.; Zhang, T.; Ma, J. (Fly, 2016)
In a recent study, we investigated the regulation of hunchback (hb) transcription dynamics in Drosophila embryos. Our results suggest that shutdown of hb transcription at early nuclear cycle (nc) 14 is an event associated with the global changes taking place during the mid-blastula transition (MBT). Here we have developed a simple model of hb transcription dynamics during this transition time. With kinetic parameters estimated from our published experimental data, the model describes the dynamical processes of hb gene transcription and hb mRNA accumulation. With two steps, transcription onset upon exiting the previous mitosis followed by a sudden impact that blocks gene activation, the model recapitulates the observed dynamics of hb transcription during the nc14 interphase. The timing of gene inactivation is essential, as its alterations lead to changes in both hb transcription dynamics and hb mRNA levels. Our model provides a clear dynamical picture of hb transcription regulation as one of the many, actively regulated events concurrently taking place during the MBT.